Exploring the influence of educational capital on college students’ entrepreneurial performance: a moderated multi-mediation model approach - Zheng Li; Xinghua Wang; Kejun Zhang; Tian Zheng; Jianhua Zhou; Taghreed Ali Alsudais; Xiaotong Zhi (Humanities & Social Sciences Communications)
Abstract Entrepreneurship education significantly enhances college students’ entrepreneurial abilities, yet its intricate impact on entrepreneurial performance remains largely unexplored. Addressing this research gap, our study analyzed 2179 entrepreneurial college students from four provinces in mainland China using a structural equation model. We investigated how educational capital—comprising human capital, social capital, and psychological capital—influences entrepreneurial performance, which encompasses financial performance, growth performance, and innovation performance. Our findings revealed that educational capital directly boosts entrepreneurial performance and indirectly affects it through the mediation of entrepreneurial training, which includes opportunity identification, team building, resource acquisition, and strategic planning. Additionally, social support plays a crucial moderating role in the relationship between educational capital and entrepreneurial training. These results underscore the importance of educational capital accumulation and transformation for improving entrepreneurial performance, with entrepreneurial training and social support serving as pivotal factors. Our study offers fresh insights into the impact mechanism of entrepreneurship education on entrepreneurial performance and suggests new avenues for optimizing such education.